Respuesta :

your answers are wrong. the function f(x) is like a factory. you put in something ( a number) and it will spit you out something else (a different number depending on the function). your function, f (x)= -2x+1

you can put anything in that function. let say k.
f(x=k) = -2k+1. you just replace the x with k.
in this particular problem they way f(-2) ,f(0), f(1) and f(2).
here are the results
f(x=-2) = f(-2) = -2×(-2)+1 =5
f(x=0) = f(0) = -2×(0)+1 =1
f(x=1) = f(1) = -2×(1)+1 =-1
f(x=2) = f(2) = -2×(2)+1 =-3